Variability in the Processing of Fresh Osteochondral Allografts - Paul, Kyle D.; Patel, Romil K.; Arguello, Alexandra M.; Kwapisz, Adam; Brabston, Eugene W.; Stannard, James P.; Ponce, Brent A.; Momaya, Amit M. (The Journal of Knee Surgery, 2021)
The indications for fresh osteochondral allograft continue to increase. As a result, variations in graft processing and preservation methods have emerged. An understanding of these techniques is important when evaluating the optimal protocol for processing fresh osteochondral allografts prior to surgical implantation. The aim of this study is to review the literature and understand various tissue processing protocols of four leading tissue banks in the United States. Donor procurement, serological and microbiological testing, and storage procedures were compared among companies of interest. Similarities between the major tissue banks include donor screening, aseptic processing, and testing for microorganisms. Variability exists between these companies with relation to choice of storage media, antibiotic usage, storage temperature, and graft expiration dates. Potential exists for increased chondrocyte viability and lengthened time-to-expiration of the graft through a protocol of delicate tissue handling, proper choice of storage medium, adding hormones and growth factors like insulin growth factor-1 (IGF-1) to serum-free nutrient media, and storing these grafts closer to physiologic temperatures.
Keywords: allograft; processing; storage; chondrocyte; viability